EVALUASI KEPUASAN PELANGGAN DIBELMOND JIMBARAN PURI BALI MELALUI LEADING QUALITY ASSURANCE - Astawa, I Ketut; Suardani, Anak Agung Putri; Istiarto, Istiarto (Valid Jurnal Ilmiah, 2017)
Improving customers’ satisfaction is important in the hospitality industry. On the other hand, quality services encourage customer satisfaction. Therefore, offering product (tangible) and services (intangible) to customers need to be standardized.Belmond Jimbaran Puri Bali committed to excellent serviceby implementingLeading Quality Assurance (LQA) standard.LQA standard is specializes in providing quality assurance audits, benchmarking analysisand training services to the luxury hospitality industry. This research is aiming to evaluatethe implementation of LQA standard to improve the customers’ satisfaction in front office department. Data is analysed by using Context, Input, Process, and Output (CIPP) method and supported by SPSS 17.0for windows. The finding of implementing LQA standard is in excellent categories. The finding proved that LQA standard is well implemented by Belmond Jimbaran Puri Bali management